The Local Festival of Kampos: A Fictional Narrative of Place, Space and Interiority - Vidali, Maria (Interiority, 2020)
This article is created out of the architectural space and narratives of village life. The narratives concern the interiority of life in Kampos, a farming village on the Greek Cycladic island of Tinos, on the day when the village celebrates the Holy Trinity, its patron saint. The village area on this festive day is depicted in the movement of the families from their houses to the church, the procession from the patron saint’s church to a smaller church through the main village street, and, finally, in the movement of the villagers back to speci!c houses. Through a series of spatial and social layers, the meaning of the communal table on the day of the festival, where food is shared, is reached. A series of negotiations create a different space, where the public, private and communal blend and reveal different layers of “interiority” through which this community is bounded and connected. In this article, I follow the revelation and discovery of truth through fiction, story or myth, as argued by the French philosopher Paul Ricoeur.